Cell paintballing using optically targeted coacervate microdroplets. Issue 11 (5th August 2015) - Armstrong, James P. K.; Olof, Sam N.; Jakimowicz, Monika D.; Hollander, Anthony P.; Mann, Stephen; Davis, Sean A.; Miles, Mervyn J.; Patil, Avinash J.; Perriman, Adam W.
Abstract : A dynamic holographic assembler was used to "paintball" stem cells with coacervate microdroplets loaded with protein, oligonucleotide or molecular dye. Abstract : We present a new approach for the directed delivery of biomolecular payloads to individual cells with high spatial precision. This was accomplished via active sequestration of proteins, oligonucleotides or molecular dyes into coacervate microdroplets, which were then delivered to specific regions of stem cell membranes using a dynamic holographic assembler, resulting in spontaneous coacervate microdroplet–membrane fusion. The facile preparation, high sequestration efficiency and inherent membrane affinity of the microdroplets make this novel "cell paintballing" technology a highly advantageous option for spatially-directed cell functionalization, with potential applications in single cell stimulation, transfection and differentiation.